The Development of the Food Market as a Factor in Increasing Regional Competitiveness - S. S. Voronkov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The article discusses the main provisions of the modern regional competitiveness, investigated a number of indicators used to assess regional competitiveness. In terms of the quality of life of the population, the criterion for assessing the level of development of a regional food market is highlighted, complementing the system of indicators for assessing the level of regional competitiveness in a region. The external and internal factors influencing the development of the regional food market at the current stage of its development are determined. The criteria for the formation of a food market strategy as a tool for increasing regional competitiveness are formulated.Aim. Identify the need to include criteria for the development of a regional food market in the system of criteria for assessing regional competitiveness.Tasks. Consider the factors of regional competitiveness, determine the place of the factor of development of the regional food market in the general system of factors. Formulate criteria for the development of a regional food market factor.Methods. The methodological basis of the work was general scientific methods, domestic and international research in the field of regional competitiveness and the development of the food market.Results. The paper identifies a group of indicators for assessing regional competitiveness. The rationale for including the criterion for the development of a regional food market in the system of indicators for assessing regional competitiveness has been formulated. The structure of the evaluation of the criterion for the development of a regional food market to increase the level of regional competitiveness has been determined.